1985
DOI: 10.1111/j.1600-0765.1985.tb00838.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of daily treatments with an octenidine dentifrice formulation on gingival health in Cynomolgus monkeys

Abstract: Octenidine, a bispyridine antimicrobial compound, has evidenced significant antiplaque activity when used in solution in both animal and human model systems. The present study was designed to evaluate concurrently the antiplaque and antigingivitis potential of a dentifrice formulation containing octenidine. In addition to an antimicrobial agent, the product was formulated to exhibit abrasive and foaming chracteristics similar to those of current commercial dentifrices. Adult female cynomolgus monkeys, five per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This model bas been used to test the efficacy of agents to prevent the accumulation of plaque and thereby delay the onset of gingivitis during 21 days of tootbbrushing abstention. Mouthwashes containing Chlorhexidine (7), Oetenidine (8) and Sanguinarine (9), as well as a phenolic mouthwash (10) have been demonstrated to delay the onset of gingivitis. Tbese same materials were later shown to have gingival health benefits in longer term studies combining both mouthrinsing and normal toothbrushing (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…This model bas been used to test the efficacy of agents to prevent the accumulation of plaque and thereby delay the onset of gingivitis during 21 days of tootbbrushing abstention. Mouthwashes containing Chlorhexidine (7), Oetenidine (8) and Sanguinarine (9), as well as a phenolic mouthwash (10) have been demonstrated to delay the onset of gingivitis. Tbese same materials were later shown to have gingival health benefits in longer term studies combining both mouthrinsing and normal toothbrushing (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In dental practice, the main usage of OCT is as a mouth rinse material and the antimicrobial/ antiplaque effect thereof has been demonstrated in several studies. [16][17][18][19][20][21][22] It is reported that OCT inhibits dental plaque and caries in rats, dental plaque in primates, and in humans. [16][17][18][19] Pitten and Kramer 20 showed that OCT has antimicrobial efficiency in oral cavities.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] It is reported that OCT inhibits dental plaque and caries in rats, dental plaque in primates, and in humans. [16][17][18][19] Pitten and Kramer 20 showed that OCT has antimicrobial efficiency in oral cavities. On the other hand, Shern et al 17 compared OCT and CHX as a mouth rinse solution in rats and found no statistical difference between the effect of OCT and CHX in dental plaque and dental carries formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…
Muramyl dipeptide (MDP) analogues were prepared and utilized in the synthesis of new fluorescently labeled MDP derivatives for use as biologic probes. Thus, jVa-(jV-acetylmuramyl)-L-lysyl-D-isoglutamine (Lys-MDP, 4) and iVa-(jV-acetylmuramyl)-L-alanyl-D-isogutaminyl)-L-lysine [MTP,5] were synthesized and then reacted with 2-(fluoresceinylamino)-4,6-dichloro-s-triazine (DTAF, 2) to yield the fluorescent adducts, DTAF-Lys-MDP ( 6) and DTAF-MTP (7). The adjuvant activity of the fluorescent MDP derivatives was determined by the ability of the compounds to promote delayed skin test responses in guinea pigs immunized with ovalbumin (OA) and by evaluating the anti-OA activity of these guinea pigs.
…”
mentioning
confidence: 99%